Quantum Teaching Dan Quantum Learning Dalam Pembelajaran - Wagiman Manik; Alvaro Gusty Ivanatha; Habib Syuhada; Yilmazer Maldini; Muhammad Fajrul Islam; Zul Fahmi Rambe (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The advancement of science and technology has significantly impacted the education sector. Quantum Teaching and Quantum Learning emerge as innovative approaches that optimize teacher-student interactions to create effective learning experiences. Quantum Learning emphasizes enjoyable learning, while Quantum Teaching focuses on teaching strategies that build student motivation through suggestive approaches. These methods are developed from various theories, such as Suggestology, Accelerated Learning, and Neuro-Linguistic Programming (NLP). Research findings indicate that implementing Quantum Teaching and Quantum Learning enhances learning motivation, creativity, and academic performance. Therefore, these methods are highly relevant for educational systems to foster a more interactive and enjoyable learning environment.